THE ANALISIS MISKONSEPSI SISWA SMA PGRI PEKANBARU PADA MATERI ASAM BASA MENGGUNAKAN TES DIAGNOSTIK FOUR-TIER - siska siska; Pangoloan Soleman Ritonga (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
This research aimed at knowing whether there was or not student misconception and its percentage on acid base using Four-Tier diagnostic test materials. The acid base material is one of the chemistry materials that was always misconceiving. This research was a descriptive qualitative. Purposive sampling technique was used for obtaining the sample. The subject of this research was the XI grade of science students of senior high school PGRI Pekanbaru. Observation, FourTier diagnostic tests, interview and documentation techniques were used for collecting the data. The findings of this research showed that there was misconception on acid base material (55%). The misconception happened on all concepts, acid base theoretical concept was 56%, acid base indicator was 53%, acid base strength was 53%, the ionization constant of acids bases (ka/kb) were 70%, pH solution calculation was 50% and pH concept in environment was 54%. The average percentage of student understanding concept was in class XI grade of science students of senior high school PGRI Pekanbaru on acid-base material was 11% students understand the concept, 55% of student experience misconceptions with moderate criteria, 33% of student do not understand the concept, and 1% of student have an Error.